Economic Losses Estimation of Pathogenic Escherichia coli Infection in Indonesian Poultry Farming - Freshinta Jellia Wibisono; Bambang Sumiarto; Tri Anggraeni Kusumastuti (Buletin Peternakan, 2018)
This study aims to calculate the estimated economic losses in national poultry farming in Indonesia that are infected with pathogenic Escherichia coli. Poor management of chicken preservation is a major predisposing factor. Escherichia coli is a normal flora found in the gastrointestinal tract of chicken, but when the chicken stress or decrease immune system, Escherichia coli develops into a pathogenic agent. Pathogenic Escherichia coli appears as secondary infections that aggravate other disease infection. Cost of illness approach was divided into two main categories namely direct losses from disease and indirect losses from other related costs. Direct losses in broiler farms that were infected with pathogenic Escherichia coli through calculation of weight loss of harvest and total mortality, while in layer farms that were infected with pathogenic Escherichia coli, direct loss calculations included decreased chicken egg production and total mortality. Indirect losses on broiler and layer farms included calculation of other expenditure costs at the time of the occurrence of pathogenic Escherichia coli infections such as cleaning, disinfection and labor compensation costs. Based on the total calculation results obtained that the estimated economic losses incurred on national scale broiler farms reached IDR 14,167,792,041,150, - per harvest period of broiler, while estimated total loss of layer farms on national scale based on the calculation results reached IDR 13,391,996,617,850, - per month. The overall total loss due to this colibacillosis reached 13.10% of total poultry assets in Indonesia. The large proportion of losses incurred to total livestock assets can indicate how important the disease is to be controlled or overcome.